2014
DOI: 10.1016/j.nuclphysb.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Energy–pressure relation for low-dimensional gases

Abstract: A particularly simple relation of proportionality between internal energy and pressure holds for scale-invariant thermodynamic systems (with Hamiltonians homogeneous functions of the coordinates), including classical and quantum -Bose and Fermi -ideal gases. One can quantify the deviation from such a relation by introducing the internal energy shift as the difference between the internal energy of the system and the corresponding value for scale-invariant (including ideal) gases.After discussing some general t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…In textbooks it is usually derived by the integration by parts of the free energy, Ω = − P V . On the other hand, it can be shown that [16], this relation is a consequence of the scale invariance of the Hamiltonian with respect to the dilation of coordinates such as r → λr.…”
Section: B Ideal Optical Latticementioning
confidence: 99%
“…In textbooks it is usually derived by the integration by parts of the free energy, Ω = − P V . On the other hand, it can be shown that [16], this relation is a consequence of the scale invariance of the Hamiltonian with respect to the dilation of coordinates such as r → λr.…”
Section: B Ideal Optical Latticementioning
confidence: 99%
“…Therefore, the equations derived here also apply in the case of inverse square potentials in arbitrary spatial dimension and other SO(2, 1) invariant systems such as anyons [37][38][39][40][41][42].…”
Section: Comments and Conclusionmentioning
confidence: 99%
“…The formal mathematical steps in the general case presented here are the same as in that paper, and Eq. (24) would become 6 We are now restricting ourselves to radial potentials. 7 As an example, consider…”
Section: Conclusion and Commentsmentioning
confidence: 99%
“…(9), can be recast into a different form that illustrates the effect of microscopic scales on the thermodynamics of a system. A simple way to see this is to write the potential as 6 :…”
mentioning
confidence: 99%